Design of PLC-based Control System for 18650 Lithium-ion Battery Dismantling Machine. Issue 1 (May 2020) - Hadiwibowo, Suryo; Wisambodhi, Satria Mahardhika; Mahardika, Muslim; Perdana, Indra
Abstract: The dismantling process of 18650 lithium-ion battery aims to separate the shell from its contents that contain lithium. The dismantling process is carried out using pneumatic components that automated by using a programmable logic controller (PLC). This research was conducted through 5 stages of the process, namely: machine designing and manufacturing, pneumatic system designing, PLC control designing, assembly, and testing. The design of pneumatic systems and their control is carried out to get the easiest and most effective working system.